2017
DOI: 10.1117/12.2253645
|View full text |Cite
|
Sign up to set email alerts
|

Minimally invasive optical biopsy for oximetry

Abstract: The study of localised oxygen saturation in blood vessels can shed light on the etiology and progression of many diseases with which hypoxia is associated. For example, hypoxia in the tendon has been linked to early stages of rheumatoid arthritis, an auto-immune inflammatory disease. Vascular oximetry of deep tissue presents significant challenges as vessels are not optically accessible. In this paper, we present a novel multispectral imaging technique for vascular oximetry, and recent developments made toward… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 19 publications
(16 reference statements)
0
5
0
Order By: Relevance
“…MSI oximetry has been applied to diverse applications in vivo, including measurement of blood OS in the spinal cord [7], the brain [8], muscle tendons [9,10], the bowel [11], the oral microvasculature [12], and the skin [13]. In the eye, MSI oximetry has established the oxygen dynamics and physiological norms of the retina [6], the choroid [14], the bulbar conjunctiva [15], and the episcleral blood vessels [15].…”
Section: The Application and Utility Of Multispectral Imaging (Msi) O...mentioning
confidence: 99%
See 4 more Smart Citations
“…MSI oximetry has been applied to diverse applications in vivo, including measurement of blood OS in the spinal cord [7], the brain [8], muscle tendons [9,10], the bowel [11], the oral microvasculature [12], and the skin [13]. In the eye, MSI oximetry has established the oxygen dynamics and physiological norms of the retina [6], the choroid [14], the bulbar conjunctiva [15], and the episcleral blood vessels [15].…”
Section: The Application and Utility Of Multispectral Imaging (Msi) O...mentioning
confidence: 99%
“…Their study concluded that if the tissue surrounding a vessel is illuminated, then the vessel will be effectively back-illuminated [58]. This finding has subsequently been used to simplify multispectral oximetry models by enabling the use of annular illumination to eliminate double-pass contributions in MSI oximetry models [9,70].…”
Section: Optical Paths Through Blood Vesselsmentioning
confidence: 99%
See 3 more Smart Citations